The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1346-8138.2010.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiolymphoid hyperplasia with eosinophilia affecting the scrotum: A rare case report with molecular evidence of T‐cell clonality

Abstract: Angiolymphoid hyperplasia with eosinophilia (ALHE) is a rare, benign entity of unknown pathogenesis. It often presents as painful or pruritic intradermal or subcutaneous red to brown papules or nodules on the head and neck of young adults. A 38-year-old man had a gradually enlarging and mild pruritic plaque on the scrotum for half a year. Pathological findings showed dermal proliferation of anomalous blood vessels lined by plump endothelium with a significant perivascular inflammatory infiltrate composed of ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
0
12
1
2
Order By: Relevance
“…The etiology and pathogenesis of ALHE is still unknown; however, researcher believed that this entity is formed due to vascular malformation. Some cases of ALHE have been connected into trauma history and Human T‐cell Lymphotropic virus (HTLV) or Human Herpesvirus 8 (HHV‐8) infection …”
Section: Discussionmentioning
confidence: 99%
“…The etiology and pathogenesis of ALHE is still unknown; however, researcher believed that this entity is formed due to vascular malformation. Some cases of ALHE have been connected into trauma history and Human T‐cell Lymphotropic virus (HTLV) or Human Herpesvirus 8 (HHV‐8) infection …”
Section: Discussionmentioning
confidence: 99%
“…Nadiren yaygın lezyonlar görülebilmektedir. 8,9 Bazen derin yumuşak dokuları tutmakta ya da derin damarlardan kaynaklanmaktadır. 7 Serum hipereozinofili ve bölgesel lenfadenomegali gö-rülmektedir, ancak tanı için gerekli değildir.…”
Section: Discussionunclassified
“…Başka bir güncel bildiride skrotum lokalizasyonlu EAH hastasında T-hücre klonalitesi gösterilmiştir. 9 İlginç olarak, iki EAH raporunda birbirini izleyen ya da metasenkron olarak tanı, almış periferal T-hücre lenfoması olması, EAH'nin erken form bir lenfoma olabileceği sorusunu akla getirmiştir. 12,14 Ancak hastaların büyük çoğunluğunun benign karakterde olduğu vurgulanmaktadır.…”
Section: Discussionunclassified
“…On the other hand, others considered these lesions as neoplastic [7]. Previous papers have reported that these masses are consisted of mostly CD3-positive T cells [8] with monoclonality [9]. …”
Section: Discussionmentioning
confidence: 99%